Muscle anisotropy influences the phrenic nerve activation threshold in non-invasive electrical stimulation - Laureen Wegert; Marek Ziolkowski; Alexander Hunold; Tim Kalla; Irene Lange; Jens Haueisen (Medical & Biological Engineering & Computing, 2026)
Objective Electric phrenic nerve stimulation is employed as a method of artificial ventilation, and computational models are utilized to assist in parameter selection. The majority of models assume isotropic tissue conductivity, although muscle tissue exhibits anisotropic properties. We aim to investigate the influence of anisotropic muscle conductivity on the results of phrenic nerve activation. Methods To calculate the potential distribution, we used an anatomically detailed multi-scale model for non-invasive electrical stimulation in the neck, incorporating realistic muscle fiber orientations. Phrenic nerve activation thresholds were calculated using the McIntyre-Richardson-Grill nerve model. Anisotropy ratios ranging from 1:1 to 1:15 (transversal:longitudinal conductivities) were analyzed at constant corresponding isotropic conductivity. Additional simulations assessed the influence of muscle volume and electrode placement and quantified possible co-activation of other nerves in the neck. Main results Increasing anisotropy ratios resulted in consistently higher phrenic nerve activation thresholds across all axon diameters (up to + 90%). Larger muscle volumes and electrode positions directly over a muscle further elevated the anisotropy effects. Considering anisotropic muscle conductivity increases the number of co-activated nerves. Conclusion High-resolution models incorporating anisotropic conductivity are recommended for research studies on phrenic nerve stimulation.

Environmental conditions and carbonate chemistry variability influencing coral reef composition along the Pacific coast of Costa Rica - Celeste Sánchez-Noguera; Ines D. Lange; Jorge Cortés; Carlos Jiménez; Christian Wild; Tim Rixen (Frontiers in Marine Science, 2025)
Coral reef development is influenced by a wide variety of factors, including temperature, salinity, nutrient concentrations, and carbonate chemistry. Studies focusing on physicochemical drivers of coral reef distribution and composition in the Eastern Tropical Pacific (ETP) are scarce, and carbonate chemistry and nutrient data for this region are limited. This study measured coral reef composition and physicochemical parameters along the Pacific coast of Costa Rica, over a one-year period at three locations: Santa Elena and Matapalo in the north, and Parque Nacional Marino Ballena in the south. Our results show high seasonal and spatial variability of physicochemical conditions with significant differences mainly explained by inorganic nutrient concentrations, with driving processes also having a strong influence on the variability of carbonate chemistry parameters. Coastal upwelling is the main driver of the seasonal variability in Santa Elena. Comparison of seasonal dissimilarity within locations confirms the presence of a geographical gradient, with stronger influence of the upwelling in Santa Elena relative to Matapalo, where several parameters displayed a lower seasonality and a carbonate system that supports reef development throughout the year. Conversely, in Marino Ballena the river discharges during rainy season exerted a strong control on the seasonal variability. The integrated analysis of coral reef composition and physicochemical parameters suggests that in addition to inorganic nutrients carbonate chemistry also plays a key role in coral distribution. Analyzing the spatial distribution of the main reef builders provides insights into the species-specific tolerance to varying conditions. Pavona clavus is widely distributed in both the northern and southern locations, suggesting that this massive coral is very tolerant to the high variability of physicochemical conditions. The dominant corals in the north ( Pavona gigantea and Pocillopora spp.) are highly tolerant to nutrient-enriched cold waters with low aragonite saturation, while one of the main reef-builders in southern locations ( Porites cf. lobata ) cope better with low salinity, low aragonite saturation and low light intensity caused by river discharges. Understanding the preferences of individual coral species at our study locations can shed light on the environmental factors driving coral reef distribution in other locations of the ETP.

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Validation of GEMS operational v2.0 total column NO2 and HCHO during the GMAP/SIJAQ campaign - Kangho Bae; Chang-Keun Song; Michel Van Roozendael; Andreas Richter; Thomas Wagner; Alexis Merlaud; Gaia Pinardi; Martina M. Friedrich; Caroline Fayt; Ermioni Dimitropoulou; Kezia Lange; Tim Bösch; et al. (Science of The Total Environment, 2025)

Metastasis-directed stereotactic radiotherapy in patients with breast cancer: results of an international multicenter cohort study - Alexander Fabian; Daniel Buergy; Fabian Weykamp; Juliane Hörner-Rieber; Denise Bernhardt; Judit Boda-Heggemann; Montserrat Pazos; Nora Mehrhof; David Kaul; Alicia S. Bicu; Eugenia Vlaskou Badra; Susanne Rogers; et al. (Clinical & Experimental Metastasis, 2025)
Metastasis-directed therapy (MDT) for oligometastatic breast cancer (≤ 5 metastases) has shown little effect in specific scenarios of randomized trials. Therefore, we aimed to assess outcomes after metastasis-directed stereotactic radiotherapy (SRT) in various clinical scenarios. We conducted an international retrospective cohort study in thirteen centers including breast cancer patients receiving SRT to any metastatic site. Outcomes included local recurrence (LR), progression-free survival (PFS), and overall survival (OS). Cumulative incidence analysis was used for LR, Kaplan–Meier estimates for PFS and OS. Covariables included patient, disease, and SRT characteristics. We performed univariable and multivariable analyses (MVA). Among 444 patients, 751 metastases were treated with SRT. Of these, 73% were intracranial and 27% extracranial lesions. Oligometastatic disease (OMD) was present in 66% of the patients. LR after two years occurred significantly more often in intracranial (25%) versus extracranial lesions (7%). In MVA of patients with OMD treated for intracranial sites, higher performance status was significantly associated with longer PFS. Further, higher performance status, biologic subtype (HR-pos./HER2-pos.), and MDT to all sites were significantly associated with longer OS. In MVA of oligometastatic patients treated for extracranial sites, biologic subtype (HR-neg./HER2-pos.) and synchronous metastasis were associated with significantly longer PFS, whereas higher grading was associated with significantly shorter PFS. Moreover, biologic subtype (HR-neg./HER2-neg.) was associated with significantly shorter OS. In conclusion, the role of MDT for breast cancer may vary per clinical scenario. Patients with OMD treated for intracranial lesions who had MDT to all sites showed superior OS. Our results should be validated prospectively.

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Land-use experts’ perception of regional climate change: an empirical analysis from the North German Plain - Tim Barkmann; Rosemarie Siebert; Andrej Lange (Climatic Change, 2017)

Klimatischbedingte Anpassungsstrategien für ein Talsperrenverbundsystem im Harz - Günter Meon; Tim Müller; Andreas Koch; Frank Eggelsmann; Lisa Unger; Andreas Lange (WASSERWIRTSCHAFT, 2016)

Einsatz der Quelltermmethode bei Hochwasserschutzkonzeptionen im ländlichen Raum - Carsten Lange; Reinhard Hinkelmann; Martin Lindenberg; Tim Fröhlich (WASSERWIRTSCHAFT, 2012)

Effects of two different dosing regimens of terlipressin on organ functions in ovine endotoxemia - Matthias Lange; Christian Ertmer; Sebastian Rehberg; Andrea Morelli; Gabriele Köhler; Tim G. Kampmeier; Hugo Van Aken; Martin Westphal (Inflammation Research, 2011)

Differential threshold effects of habitat fragmentation on gene flow in two widespread species of bush crickets - REBECCA LANGE; WALTER DURKA; STEPHANIE I. J. HOLZHAUER; VOLKMAR WOLTERS; TIM DIEKÖTTER (Molecular Ecology, 2010)
Effects of habitat fragmentation on genetic diversity vary among species. This may be attributed to the interacting effects of species traits and landscape structure. While widely distributed and abundant species are often considered less susceptible to fragmentation, this may be different if they are small sized and show limited dispersal. Under intensive land use, habitat fragmentation may reach thresholds at which gene flow among populations of small‐sized and dispersal‐limited species becomes disrupted. Here, we studied the genetic diversity of two abundant and widespread bush crickets along a gradient of habitat fragmentation in an agricultural landscape. We applied traditional ( G ST , θ ) and recently developed ( , D ) estimators of genetic differentiation on microsatellite data from each of twelve populations of the grassland species Metrioptera roeselii and the forest‐edge species Pholidoptera griseoaptera to identify thresholds of habitat fragmentation below which genetic population structure is affected. Whereas the grassland species exhibited a uniform genetic structuring ( G ST = 0.020–0.033; D = 0.085–0.149) along the whole fragmentation gradient, the forest‐edge species’ genetic differentiation increased significantly from D G ST D = 0.166 ( G ST = 0.074), once the amount of suitable habitat dropped below a threshold of 20% and its proximity decreased substantially at the landscape scale. The influence of fragmentation on genetic differentiation was qualitatively unaffected by the choice of estimators of genetic differentiation but quantitatively underestimated by the traditional estimators. These results indicate that even for widespread species in modern agricultural landscapes fragmentation thresholds exist at which gene flow among suitable habitat patches becomes restricted.

Computational object recognition: a biologically motivated approach - Tim C. Kietzmann; Sascha Lange; Martin Riedmiller (Biological Cybernetics, 2009)

Sporamin-mediated resistance to beet cyst nematodes (Heterodera schachtii Schm.) is dependent on trypsin inhibitory activity in sugar beet (Beta vulgaris L.) hairy roots - Daguang Cai; Tim Thurau; Yanyan Tian; Tina Lange; Kai-Wun Yeh; Christian Jung (Plant Molecular Biology, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)